Irfani Epistemology Imam Al-Ghazali's Perspective in Islamic Education - Nasution, Rodiah; M Sholih Salimul Uqba (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2024)
The aim of this research is to examine Al-Ghazali's Sufism thought and its correlation to education. This type of research uses library research with data and information collection methods. This research uses a qualitative descriptive approach by explaining Al-Ghazali's thoughts regarding irfani epistemology and its correlation to education. The results of this research show that in essence Al-Ghazali's Sufism teachings have a correlation with education where these teachings lead to the teachings of Al-Haqq (Allah SWT). Irfani Al Ghazali's thoughts provide valuable contributions in the educational context by emphasizing the integration of science and religion, character formation, values education, and active learning education. His holistic thinking and orientation towards moral and spiritual values can be the basis for developing education that is centered on the formation of quality and ethical individuals.